2007
DOI: 10.1080/10641960701578360
|View full text |Cite
|
Sign up to set email alerts
|

A Moderately High Fat Diet Promotes Salt-Sensitive Hypertension in Obese Zucker Rats by Impairing Nitric Oxide Production

Abstract: The objective of this research was to examine the contribution of a moderately high fat (MHF) diet to the development of salt-sensitive hypertension in obese Zucker rats. Lean and obese Zucker rats were fed either a MHF diet or a diet of standard rat chow (control diet) for 10 weeks. From week 4 through week 10, the drinking water was supplemented with 1% NaCl. Blood pressure was measured weekly, and urinary excretion of nitric oxide metabolites (NO(x)) was determined at weeks 4 and 10. At week 10, renal nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Obese rats excreted higher amount of total urinary nitrates/nitrites compared to lean rats. Consistent with previous studies, 36 excretion of urinary nitrates/nitrites, as measured on days 2 and 14 of the treatment period was greater in obese rats compared to lean rats. CGP-treatment had no effect on nitrates/nitrites excretion in lean rats but caused an increase in obese rats only during the initial (measured at 2 day) treatment period.…”
Section: Resultssupporting
confidence: 91%
“…Obese rats excreted higher amount of total urinary nitrates/nitrites compared to lean rats. Consistent with previous studies, 36 excretion of urinary nitrates/nitrites, as measured on days 2 and 14 of the treatment period was greater in obese rats compared to lean rats. CGP-treatment had no effect on nitrates/nitrites excretion in lean rats but caused an increase in obese rats only during the initial (measured at 2 day) treatment period.…”
Section: Resultssupporting
confidence: 91%
“…Endothelial dysfunction significantly contributes to the development of HF-induced hypertension (3, 6). Several studies have indicated that a HF diet induces endothelial dysfunction through the generation of oxidative stress (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Salt restriction decreased blood pressure in obese subjects more significantly than in non-obese subjects, and subjects that undergo weight loss demonstrated a suppression in salt-induced blood pressure increases (2). In rats, long treatment with a high fat (HF) diet caused greater salt-induced increases in blood pressure (35). It has also been demonstrated that endothelial dysfunction closely contributes to the development of HF diet–induced hypertension (68).…”
Section: Introductionmentioning
confidence: 99%
“…Rats fed HFD, resulted in decrease in serum and renal NO production (Table 3), indicating that obese rats are more liable to develop hypertension. Furthermore, HFD -induced defects in NO production may promote the salt-sensitivity of blood pressure, which appears to require more NO to maintain blood pressure during a salt challenge [50]. …”
Section: Discussionmentioning
confidence: 99%